Brief Report: JNK‐2 Controls Aggrecan Degradation in Murine Articular Cartilage and the Development of Experimental Osteoarthritis. Issue 5 (27th April 2016) - Ismail, Heba M.; Miotla‐Zarebska, Jadwiga; Troeberg, Linda; Tang, Xiaodi; Stott, Bryony; Yamamoto, Kazuhiro; Nagase, Hideaki; Fosang, Amanda J.; Vincent, Tonia L.; Saklatvala, Jeremy
Abstract : Objective: The pathogenesis of osteoarthritis (OA) is poorly understood. Loss of the proteoglycan aggrecan from cartilage is an early event. Recently, we identified a role for the JNK pathway, particularly JNK‐2, in human articular chondrocytes in vitro in regulating aggrecan degradation. The present study was undertaken to investigate whether JNK‐2 has a similar function in vivo and to examine its role in gene expression. Methods: Aggrecan fragments were analyzed by Western blotting. OA was induced by destabilization of the medial meniscus (DMM) and assessed at 4, 8, and 12 weeks after surgery. Knee sections were stained with Safranin O. Medial compartments were scored by histologic grading for aggrecan loss and cartilage damage. RNA was extracted from JNK‐2 −/− and wild‐type mouse knees 6 hours after DMM or after interleukin‐1 stimulation of the proximal epiphysis, and expression of 33 DMM‐regulated genes was analyzed with quantitative polymerase chain reaction–customized array cards. Results: In vitro, basal and interleukin‐1– or tumor necrosis factor–stimulated release of aggrecanase‐generated aggrecan fragments was greatly reduced in cartilage from JNK‐2 −/− mice. In the OA model, JNK‐2 −/− mice exhibited significant reduction of aggrecanase‐generated fragments and cartilage damage. Of 33 genes investigated, 13 were significantly down‐regulated in JNK‐2 −/− mice compared with wild‐type mice, following DMM. These included Has1, Adamts4, Tnf, Il6, Il18, Il18rap, Il1a, Inhba, Cd68, Ngf, Ccr2, Wnt16, and Tnfaip6, but not Adamts5 . Conclusion: Our results demonstrate that JNK‐2 regulates aggrecan degradation in cultured murine cartilage and surgically induced OA in vivo following mechanical destabilization of the knee joint. This implicates the JNK signaling pathway in OA and suggests potential novel approaches to therapy.